Price of Solar PV Electricity in Developing Countries - Dobrotkova, Zuzana (World Bank, Washington, DC, 2020)
The purpose of this paper is to help stakeholders to understand key factors driving utility-scale solar PV prices and enable good decision-making conducive to healthy development of solar PV sector globally. This analysis allows us to determine whether recently announced prices are realistic under local conditions like insolation, costs of equipment, access to financial markets, and other project-related variables. The authors also discuss whether these prices are sustainable over time and allow further healthy market expansion.